Aplikasi Pembelajaran Berbasis WEB - SW, Denni Figo; Setiawan, Cevin Eris; Widyassari, Adhika Pramita (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2023)
Web-Based Learning System entitled Introduction to Tatasurya is one of the web-based learning media. The learning system aims to make it easier for students to learn about the introduction of the solar system. Designing a web-based learning system entitled Introduction to Tatasurya using PowerPoint software, website 2 APK builder Pro and HTML programming language. The results of the discussion show that the wab-based learning system entitled Introduction to the Solar System is feasible to use in the learning process. This is based on an average value of 83.3% from 100% so that the application can run properly.